2021
DOI: 10.1101/2021.04.26.441431
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Refining the genomic location of SNP variation affecting Atlantic salmon maturation timing at a key large-effect locus

Abstract: Efforts to understand the genetic underpinnings of phenotypic variation often lead to the identification of candidate regions showing signals of association and/or selection. These regions may contain multiple genes and therefore validation of which genes are actually responsible for the signal is required. In Atlantic salmon (Salmo salar), a large-effect locus for maturation timing occurs in a genomic region including two candidate genes, vgll3 and akap11, but data for clearly determining which of the genes (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

6
0

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…In addition to underlying body condition variation may vgll3 also directly be involved in gonadal development via inhibition (Kjaerner‐Semb et al, 2018), whereby the different alleles associate with the expression variation of specific isoforms that may vary in their degree of maturation inhibition (Verta et al, 2020). Nonetheless, a final conclusion from our tentative results requires additional research, also because other plausible candidate genes close to vgll3 have been identified, such as akap11 (Ayllon et al, 2015; Barson et al, 2015; but see Sinclair‐Waters et al, 2021).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In addition to underlying body condition variation may vgll3 also directly be involved in gonadal development via inhibition (Kjaerner‐Semb et al, 2018), whereby the different alleles associate with the expression variation of specific isoforms that may vary in their degree of maturation inhibition (Verta et al, 2020). Nonetheless, a final conclusion from our tentative results requires additional research, also because other plausible candidate genes close to vgll3 have been identified, such as akap11 (Ayllon et al, 2015; Barson et al, 2015; but see Sinclair‐Waters et al, 2021).…”
Section: Discussionmentioning
confidence: 85%
“…Nonetheless, a final conclusion from our tentative results requires additional research, also because other plausible candidate genes close to vgll3 have been identified, such as akap11(Ayllon et al, 2015;Barson et al, 2015; but seeSinclair-Waters et al, 2021).…”
mentioning
confidence: 88%
“…Atlantic salmon used for this study were a subset of individuals used in Sinclair-Waters et al, 2021. Offspring used for this study were selected from a single family resulting from crossing unrelated parents (Kymijoki origin, F1 hatchery generation) with heterozygous (vgll3*EL) genotypes, thus enabling assessment of expression patterns of all vgll3 genotypes within a similar genetic background.…”
Section: Animal Materials and Genotypingmentioning
confidence: 99%
“…In Atlantic salmon, the vestigial-like family member 3 gene (vgll3) is strongly associated with maturation timing in the wild in both sexes but also exhibits sex-specific maturation effects (Barson et al, 2015;Czorlich et al, 2018). This association between vgll3 and maturation probability has been subsequently validated in one year-old males in common garden settings (Debes et al, 2021;Sinclair-Waters et al, 2021;Verta et al, 2020). This makes vgll3 a potential candidate regulating reproductive axis genes in place of the absent gnrh1, however, the molecular details of the action of vgll3 on reproductive axis genes has remained unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…A fin clip was taken from the caudal fin and stored in ethanol for verifying the vgll3 genotype and for sex determination. We used Kompetitive allelespecific polymerase chain reaction (KASP TM , LGC, UK) assays (He et al, 2014) for the vgll3TOP SNP and the sex-specific SDY locus as described in (Sinclair-Waters et al, 2021).…”
Section: Respirometry Detailsmentioning
confidence: 99%